PENINGKATAN HASIL PERTANIAN KELOMPOK WANITA TANI DI DESA LUMBAN TOBING KAB. HUMBANG HASUNDUTAN: Increasing Agricultural Results of Women Farmers' Group in Lumban Tobing Village Humbang Hasundutan Regency - Purba, Angelia M; Simatupang, Eva M; Purba, Arlina P; Heddy, Heddy (PUAN INDONESIA, 2024)
The current conditions are that partners still use conventional methods in processing land, namely using hoes and rakes, while the land that must be cultivated is 17,800 m2 – 22,600 m2 / person. If you use manual methods, what happens is that a lot of land cannot be cultivated optimally, so that the productivity of agricultural products is not optimal. The purpose of using a cultivator in tillage is to create a physical condition of the soil that is suitable for plant growth with equipment that works mechanically and on a large scale. Modern agricultural equipment plays a very important role in supporting agricultural operations. Currently, almost all farmers in Indonesia have switched to using machines rather than livestock, such as buffalo and cows, to plow their fields. The reason is, modern rice cultivators can be operated on various agricultural land, ranging from dry (fields) or wet (rice fields). so that the results obtained are increasing partners' skills in using agricultural technology, both in the form of use and maintenance of these tools.Cultivate agricultural land more optimally so that the productivity of agricultural products is maximized. Partners' problems regarding human resources are resolved through the provision of 1 cultivator unit